2021
DOI: 10.1177/0194599820987458
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID‐19 Lockdown on Otitis Media With Effusion in Children: Future Therapeutic Implications

Abstract: Objective To evaluate the role of social isolation during the lockdown due to the SARS-CoV-2 outbreak (severe acute respiratory syndrome coronavirus 2) in modifying the prevalence of otitis media with effusion (OME) and the natural history of chronic OME. Study Design Retrospective study. Setting Tertiary level referral audiologic center. Methods We assessed the prevalence of OME among children aged 6 months to 12 years who attended the outpatient clinic for hearing or vestibular disorders during 2 periods bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 34 publications
6
47
0
Order By: Relevance
“…Differently, from June 2020 until April 2021 were applied restrictive measures to avoid social contacts (such as closing restaurants, schools, shops, public meeting places, etc) in according to the COVID-19 infection rate. In addition, in this period all people were required to wear a face covering outdoors and/or in public places [ 18 20 ]. Facial masks have been proven to be an effective method of protection in this pandemic, which both reduces the exhalation of virus-laden aerosols from a COVID patient and minimizes the inhalation of airborne virus-laden aerosols by the subjects surrounding the patient [ 12 , 17 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Differently, from June 2020 until April 2021 were applied restrictive measures to avoid social contacts (such as closing restaurants, schools, shops, public meeting places, etc) in according to the COVID-19 infection rate. In addition, in this period all people were required to wear a face covering outdoors and/or in public places [ 18 20 ]. Facial masks have been proven to be an effective method of protection in this pandemic, which both reduces the exhalation of virus-laden aerosols from a COVID patient and minimizes the inhalation of airborne virus-laden aerosols by the subjects surrounding the patient [ 12 , 17 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different studies to date have shown as obligated avoidance of interpersonal contacts, rigorous respect of the hygienic-behavioral rules, and facial masks have reduced the spread of not only of SARS-CoV-2, but also other viruses and bacteria that underlie the development of common upper respiratory diseases [ 12 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A positive effect of the Italian lockdown on middle ear disease in children was confirmed by Aldè et al [6], who documented a global reduction in the number of outpatient children with otitis media with effusion attending a pediatric audiological service in Milan during and after the lockdown, with a 93% resolution rate of chronic effusion in May-June 2020 compared to a 21% resolution rate noted in May-June 2019.…”
Section: Discussionmentioning
confidence: 84%